Manajemen Sumber Daya Manusia dalam Perspektif Islam: Tinjauan dan Implementasinya dalam Pendidikan Islam - Nurarifah, Nurarifah; Wiyanti, Sri; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyse human resource management in Islamic education and identify the obstacles faced by educational institutions in its implementation. The research method used was a literature study with a qualitative approach. Data were collected through searches and reviews of literature in the form of books, scientific articles, and relevant documents, then analysed descriptively to identify patterns and key findings related to the concepts and practices of Islamic value-based HRM. The results of the study show that HRM in Islamic education includes planning, recruitment and selection, competency development and training, as well as evaluation and empowerment of educators. The obstacles found include a shortage of competent educators, difficulties in adapting to technological developments, and a low level of understanding of the importance of targeted HRM. This study emphasises the need to strengthen Islamic-based HR management in order to produce professional educators with good character who are able to respond to current educational needs.